Vitamin D levels in the pre- and post-COVID-19 pandemic periods in pediatric patients with chronic kidney disease - Parra-Ortega, Israel; Zurita-Cruz, Jessie Nallely; Ortiz-Flores, Itzel; Romero-Navarro, Benjamin; Villasis-Keever, Miguel Angel; Martínez, Briceida López; Domínguez-Castillo, Veronica; Romo-Vázquez, José Carlos (Frontiers in Nutrition, 2023)
Introduction Vitamin D (VD) deficiency is common in children with chronic kidney disease (CKD) because of multiple factors. During the coronavirus disease 2019 (COVID-19) pandemic, it increased because of medicine shortage and no enough medical service for patients with non-COVID-19 diseases. Objective To analyze the effects of the COVID-19 pandemic-related lockdown on the serum levels and status of 25-hydroxyvitamin D3 (25-[OH]D) in children with CKD. Materials and methods This retrospective study included patients (6–18 years old) who were diagnosed with CKD stage 2–5 and routinely measured for serum VD levels between May 2019 and December 2022. Serum 25-(OH)D levels were measured before, during, and after the pandemic (2019, 2020–2021, and 2022, respectively). The daily dose of cholecalciferol supplementation and the readjustment (if required) were recorded. Results This study included 171 patients (median age: 12 years). Before the pandemic, the median serum VD level was 25.0 ng/mL (19.3% VD deficiency). Then, VD supplementation was adjusted to 400–1,200 UI daily in 98.8% (n = 169) of patients. During the pandemic, the median VD level decreased to 22.5 ng/mL (43.3% VD deficiency). Hence, the supplementation was readjusted, and after the pandemic, the level was 28.7 ng/mL (18.7% VD deficiency), indicating a statistically significant increase in serum VD levels from the prepandemic period (p = 0.007). Conclusion Decreased serum VD levels and increased VD deficiency frequency were observed in patients with CKD during the COVID-19 but improved after readjustment of supplementation.